The RANK/RANKL/OPG system in tumorigenesis and metastasis of cancer stem cell: potential targets for anticancer therapy - Sisay, Mekonnen (Onco Targets Ther, 2017)
The molecular triad involving receptor activator of nuclear factor kβ (RANK)/RANK ligand (RANKL)/osteoprotegerin cytokine system has been well implicated in several physiological and pathological processes including bone metabolism, mammary gland development, regulation of the immune function, tumorigenesis and metastasis of cancer stem cell, thermoregulation, and vascular calcification. However, this review aimed to summarize several original and up-to-date articles focusing on the role of this signaling system in cancer cell development and metastasis as well as potential therapeutic agents targeting any of the three tumor necrotic factor super family proteins and/or their downstream signaling pathways. The RANK/RANKL axis has direct effects on tumor cell development. The system is well involved in the development of several primary and secondary tumors including breast cancer, prostate cancer, bone tumors, and leukemia. The signaling of this triad system has also been linked to tumor invasiveness in the advanced stage. Bone is by far the most common site of cancer metastasis. Several therapeutic agents targeting this system have been developed. Among them, a monoclonal antibody, denosumab, was clinically approved for the treatment of osteoporosis and cancer-related diseases.